PENGARUH JUMLAH DAN KEMIRINGAN SUDU MIXER POROS VERTIKAL (VERTICAL STIRRED MIXER) TERHADAP UNJUK KERJA PENCAMPURAN - Suryadhiyanto Untung; Qiram Ikhwanul (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2018)
Mixing process use to mix liquid, viscous and granular materials. One of the common mixing devices is a vertical stirred mixer which uses a tank and a vertical shaft that rotate mixing blades. This research is done to get the effect of the blade’s number and angle inclination due to mixing performance. Mixing performance is defined as stretching and folding. The research is done by experiment. The blade’s number varies as 2, 3 and 4 blades. Blade’s inclination is varied as 90o, 80o, 70o and 60o. The blades are rotated 10 rpm. A cylinder with 18 cm diameter and 12 cm height use as mixing tank. White wall paint is used as mixing material. Black wall paint uses a tracker. Mixing processes are observed by a camera on top of the mixer. The mixing processes are arranged for 2 mixer shaft rotations. Video data are captured frame by frame and analyzed using image software. The result shows that blade’s number and angle inclination have an effect due to mixing performance. Blade’s number tends to decrease stretching and folding. Blade’s angle inclination also tends to decrease stretching and folding. Keywords: vertical stirred mixer, blade's inclination, stretching, folding